Ảnh hưởng của nhóm thế đến liên kết hiđro chuyển dời xanh trong các phức của sự tương tác giữa RCHO với CH3CHO (R = H, F, Cl, Br, CH3, NH2) - Trung, Nguyễn Tiến; Thu Trang, Nguyễn Thị; Trí, Nguyễn Ngọc; Phượng, Nguyễn Mai (Vietnam Journal of Chemistry, 2015)
Nine stable structures of the interactions between CH3CHO and RCHO (R = H, F, Cl, Br, CH3, NH2) on the potential energy surface are obtained theoretically. Their interaction energies with both ZPE and BSSE corrections at the CCSD(T)/6-311++G(d,p)//MP2/6-311++G(d,p) level of theory range from -7.47 to -12.99 kJ.mol-1. The substituents of one H atom in HCHO by one of halogens (F, Cl, Br) or CH3 group, or NH2 one make the strength of obtained complexes enhanced. In addition, the strength ordering of the complexes decreases in the order of the halogen (Br, Cl, F) derivatives via NH2 group and finally to CH3 group. The blue shifting of CH valence bond in the C-H∙∙∙O and C-H∙∙∙X (X = F, Cl, Br) hydrogen bonds decreases when replacing one H atom by one halogen atom, however it increases in the CH3 and NH2 derivative complexes. It is noteworthy that the blue shifting of CH bond in the various halogen-substituted complexes differs slightly.